Pemanfaatan Sumberdaya Hutan oleh Masyarakat di KPH Banyuwangi Utara - Bakti Abu Birgantoro; Dodik Ridho Nurrocmat (Institut Pertanian Bogor (IPB University), 2007)
Forest resource plays an important role for human life in the various aspects: socio-economy, ecology and culture. This study evaluated socio-economic condition of people around forest which affected their preferences towards the level of intensity and quantity of forest utilization. Interviews was conducted by purposive sampling during March−May 2007, focusing to the forest community in RPH Sumberwaru and RPH Sumberejo, BKPH Asembagus KPH North Banyuwangi. Most respondents were low educated-farmer that utilized various forest products such as firewood, grasses, honey, seeds (Acacia nilotica, Parkia roxburgii, Aleurites moluccana) and honey. Through this study it was revealed that total value of forest products contributed to the local community was Rp 623,044,602 annually. Two most valuable forest products for local community were grasses and firewood. Grasses for fodder contributed to 60.89% and firewood was 25.53% of the total value. Totally, forest products contributed to 25.50% and 24.80% to the total income of respondents in Sumberwaru and Sumberanyar village, respectively.Keywords: forest resource utilization, socio-economy, forest community, forest products